Comparison of FGFR1 expression on lens epithelial cells between adults and fetuses - Liu, Yu-Fu (International Journal of Ophthalmology Press, 2011)
AIM: To study the differences of fibroblast growth factor receptor 1 (FGFR1) gene on human lens epithelial cells (HLECs) of adults and fetuses. METHODS: Indirect in situ RT-PCR was adopted for detection of FGFR1 gene. The cDNA of the mRNA in the paraffin sections of fetus and adult HLEC was synthesized by reverse transcription reaction. After PCR amplification, in situ hybridization test was performed with synthesized oligonucleotide probe and relative quantification was carried out using image analysis. RESULTS: HLECs of adults and fetuses expressed FGFR1 gene, the expression level was higher in fetuses than in adults. The difference between them had significance (P<0.05). CONCLUSIONS: FGFR1 exist in HLEC and the expression is age-related, which could be one of causes of the high occurrence of post operational after-cataract in children.